Reconstructing Kinship or the pragmatics of kin talk - Zeitlyn, D (Royal Anthropological Institute of Great Britain, 1993)
This article argues that kinship terminologies are best studied in their full linguistic context; the data should be collected from naturally occurring conversation rather than elicited with frames, and recognition must be given to the fact that people choose which expressions to use. Other means are available for talking to or about kin: in any language there are many ways of referring to people. These include the use of kin terms, names, nicknames, titles and pronouns. These 'social deictic' terms are used in different social contexts. Analysis of the context shows the inadequacy of the address/reference distinction. However, the connexions between the choice of linguistic means and the social context are central to social anthropology, so new approaches must be sought. A Mambila transcript is examined, and some suggestions are made as to how a large body of conversational data could be approached in order to analyse the social deictic terms employed. The central problem for the student is to see his kinship terminology as a definite part of the dynamism of kinship relations, to determine how far the separation and combination of relatives under linguistic labels can be correlated with other sociological phenomena (Firth 1936: 226).